Retirement Behaviour in Austria: Incentive Effects on Old-Age Labor Supply - Tibor Hanappi (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2012)
This research analyses retirement behaviour in Austria based on a combined administrative dataset. Data from the Austrian social security database is merged with a dataset that contains very detailed information on all pension-relevant information on the individual level, e.g. insurance records as well as complete earnings histories. Based on this data a comprehensive microsimulation model of the Austrian pension system is developed and applied to calculate retirement benefit entitlements for each and every individual, double-checking the calculation rules with the actual, administratively calculated pension entitlements. A range of (forward-looking) incentive measures that describe the individual decision problem is constructed. Specifically, social security wealth, accrual rate, peak and option values are computed for more than 300,000 individuals within each year of the observational period (2002-2009). Based on this characterisation of the incentive structure an econometric model is developed, thus providing robust evidence for the effects of the incentive measures on old age labor supply. Simulation of several reform scenarios shows that a stronger emphasis on financial incentives in the pension system (the introduction of additional bonusses and deductions) reduces the outof-labor-force ratio of individuals aged 56-65 by 16.3% for females and 13.4% for males.
Keywords: 330; Retirement Decision; Option Value; Social Security Wealth